Awareness and Perception of Sexual Harassment among Female Adolescent Students - Shrestha, Alina; Bajracharya, Shanti (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Sexual harassment is the unwanted sexually determined behavior such as physical contact, making sexual comments, and sexual pressure whether by verbal or non-verbal actions. Sexual harassment among school adolescent girls is high, they choose to be silent after victimization without reporting due to a lack of awareness. The perception reflecting the apathy our society feels toward sexual harassment is indicated throughout our culture. The objective of the study was to find out the awareness and perception of sexual harassment among female adolescent students. Method: A descriptive cross-sectional study was used. Total enumerative sampling technique was used with the total sample size of 139 female adolescent students. Data was collected by using semi-structured, self-administered questionnaires. Descriptive and inferential statistics were used to analyze and interpret the findings using SPSS version 16. Result: The findings of the study revealed that more than one-fourth (28.1%) of the respondents had a high level of awareness, nearly two-thirds (61.9%) had an average level of awareness and 10 % had a low level of awareness. Cent percent of the respondents had negative perceptions regarding sexual harassment. There was significant association found between levels of awareness on sexual harassment with the respondents’ parents level of education (p <0.05). Conclusion: The present study concluded that students had average level of awareness and negative perceptions on sexual harassment. Therefore, the awareness program regarding sexual harassment should be conducted with the maximum involvement of female adolescent students.